Pengaruh Media Massa Terhadap Perubahan Sosial Budaya Dan Modernisasi Dalam Pembangunan - Wawan Hernawan (KOM & REALITAS SOSIAL, 2012)
Culture is the creation of a society devoted to the interests of society in order to continue to exist and thrive. Culture reflects human responses to lifes basic needs. In terms of content or komponenya, culture can be identified into five principal, the ideas, norms of ideology, technology, and materials. The components of culture is always changing, whether the changes are slow and rapid changes in the nature. Socio-cultural changes occur because of pressure from a variety of factors, whether originating from within the community itself, as well as from outside the community. Change is a condition that we experience in every aspect of life. Like it or not, the change tends to take place every turn. In the era of information technology, a rapid change of pace. Although it seems every change promises many benefits, but it is quite clear that the promise would be realized if all the people in charge of the work was trying hard to realize that promise. communication through the mass media both print and electronic media, providing a crucial role in the political culture of social change. In line with the modernization of its speed of movement, means of communication, in this case the mass media communication needs serious attention. Planning well in the field of communications relating to software and hardware should be in line with the development of motion. This can be understood as a means of communication other than to express opinions in connection with the ideas of renewal, as well as an effective mediator in bridging the government by the people. At least three ways that can be taken by the mass media to influence cultural norms. First, mass communication messages can reinforce cultural patterns prevailing and guiding the public to believe that these patterns are still in effect and adhered to the public. Second, the media can create a new cultural patterns that do not conflict with the existing culture, and even improve it. Third, the mass media can change the cultural norms that apply to the behavior of individuals in society changed at all. These messages are not a bit of development which is distributed to the public through various media, so that people accept and support the development of movement in every aspect of life that has been programmed by the government.